A Literature Review to Examine the Validity and Reliability of Group Poster Presentations as an Assessment Method of a Module in an Undergraduate Nursing Degree Programme - McMullan, Mrs. Johanna (International Journal of Innovative Research in Medical Science, 2016)
The introduction of a poster presentation as a formative assessment method over a multiple choice examination after the first phase of a three phase “health and well-being” module in an undergraduate nursing degree programme was greeted with a storm of criticism from fellow lecturers stating that poster presentations are not valid or reliable and totally irrelevant to the assessment of learning in the module. This paper seeks to investigate these criticisms by investigating the literature regarding producing nurses fit for practice, nurse curriculum development and wider nurse education, the purpose of assessment, validity and reliability to critically evaluate the poster presentation as a legitimate assessment method for these aims.